Biographies de la Radicalisation : Des Messages Cachés du Changement Social - Bruijn, Mirjam de, 1962- (Langaa RPCIG, 2018)
Radicalization has become a word for our world in negative colors. This book seeks to understand what is radicalization in the Sahel and in the Netherlands? Is it only negative? What diversity of social and political processes lies behind this concept? The biographies of people reveal to us the hidden messages in these kinds of dynamics. Is there deep down a desire for social change? As many questions raised, answered, (partially) answered, and as many others as the reading of these collections of texts as diverse as they are interesting, will not fail to arouse the contemporary reader.